1998
DOI: 10.1159/000011898
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the c-<i>met,</i> c-<i>erbB</i>-2 and Epidermal Growth Factor Receptor Gene in Human Gastric Cancers: Correlation to Clinical Features

Abstract: We examined amplification of the c-met, c-erbB-2, and epidermal growth factor receptor (EGFR) gene in the patients with primary gastric cancer, and compared the data with clinical features in order to clarify the relationship between oncogenic abnormality and clinical features. Oncogene amplifications were examined by slot blot hybridization using DNAs extracted from formalin-fixed and paraffin-embedded tissues of primary gastric cancers. Seven of the seventy cancers (10.0%) had c-met gene amplification, nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
73
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 22 publications
8
73
0
1
Order By: Relevance
“…1,4 As mutations in the kinase domain of MET gene are almost lacking in gastric carcinomas, 5 its activation has been mostly attributed to gene amplification. [6][7][8] Although earlier Japanese reports described MET gene amplification in approximately 20% of gastric cancers by comparative genomic in situ hybridization or southern blot analysis, [9][10][11][12][13] recent FISH analyses showed rare or no amplification in locally advanced gastric carcinomas. 3,14 MET activation through copy number gain measured by quantitative real-time PCR, 3,7,8,14,15 FISH 6,14 or silver in situ hybridization, 16 and protein overexpression assessed by immunohistochemistry have been reported in gastric carcinomas.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,4 As mutations in the kinase domain of MET gene are almost lacking in gastric carcinomas, 5 its activation has been mostly attributed to gene amplification. [6][7][8] Although earlier Japanese reports described MET gene amplification in approximately 20% of gastric cancers by comparative genomic in situ hybridization or southern blot analysis, [9][10][11][12][13] recent FISH analyses showed rare or no amplification in locally advanced gastric carcinomas. 3,14 MET activation through copy number gain measured by quantitative real-time PCR, 3,7,8,14,15 FISH 6,14 or silver in situ hybridization, 16 and protein overexpression assessed by immunohistochemistry have been reported in gastric carcinomas.…”
mentioning
confidence: 99%
“…[6][7][8] Although earlier Japanese reports described MET gene amplification in approximately 20% of gastric cancers by comparative genomic in situ hybridization or southern blot analysis, [9][10][11][12][13] recent FISH analyses showed rare or no amplification in locally advanced gastric carcinomas. 3,14 MET activation through copy number gain measured by quantitative real-time PCR, 3,7,8,14,15 FISH 6,14 or silver in situ hybridization, 16 and protein overexpression assessed by immunohistochemistry have been reported in gastric carcinomas. 5,7,[17][18][19][20][21][22][23] However, there is a wide discrepancy in the incidences and prognostic significances of MET activation in gastric cancer, 3,5,7,8,[14][15][16][17][18][19][20][21][22][23][24] and correlations between copy number gain and protein overexpression have been very poor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In gastric cancer, gain-of-function mutations of MET are exceedingly rare [38][39][40], with ligand-independent activation of MET having been attributed to gene amplification [41][42][43].…”
Section: Oncogenic Met Activation In Cancermentioning
confidence: 99%
“…The prevalence of MET amplification has thus varied in the literature. Studies based on FISH analysis have identified MET amplification in up to approximately 8 % of patients with gastric cancer [42,49,67,84,88,89], whereas an increase in MET copy number has been found in up to approximately 20 % of gastric cancer patients by Southern blot analysis [41,43] or by polymerase chain reaction (PCR)-based assays [90][91][92] (Table 1). As discussed elsewhere [87], whereas Southern blot analysis and PCR-based assays measure a gain in gene copy number regardless of the underlying mechanism, FISH is able to distinguish gene amplification from polysomy.…”
Section: Future Challenges In Met Tki Therapy For Advanced Gastric Camentioning
confidence: 99%